Leptin Regulation of Gonadotrope Gonadotropin-Releasing Hormone Receptors As a Metabolic Checkpoint and Gateway to Reproductive Competence - Odle, Angela K.; Akhter, Noor; Syed, Mohsin M.; Allensworth-James, Melody L.; Beneš, Helen; Melgar Castillo, Andrea I.; MacNicol, Melanie C.; MacNicol, Angus M.; Childs, Gwen V. (Frontiers in Endocrinology, 2018)
The adipokine leptin signals the body’s nutritional status to the brain and particularly, the hypothalamus. However, leptin receptors can be found all throughout the body, including the pituitary. It is known that leptin is permissive for reproduction, and mice that cannot produce leptin (Lep/Lep) are infertile. Many studies have pinpointed leptin’s regulation of reproduction to the hypothalamus. However, leptin receptors exist at all levels of the hypothalamic-pituitary-gonadal axis. We have previously shown that deleting the signaling portion of the leptin receptor specifically in gonadotropes impairs fertility in female mice. Our recent studies have targeted this regulation to the control of GnRHR expression. The hypotheses presented here are two-fold: (1) cyclic regulation of pituitary GnRHR levels sets up a target metabolic checkpoint for control of the reproductive axis, and (2) multiple checkpoints are required for the metabolic signaling that regulates the reproductive axis. Here, we emphasize and explore the relationship between the hypothalamus and the pituitary with regards to the regulation of GnRHR. The original data we present strengthen these hypotheses and build on our previous studies. We show that we can cause infertility in 70% of female mice by deleting all isoforms of LEPR specifically in gonadotropes. Our findings implicate activin subunit (InhBa) mRNA as a potential leptin target in gonadotropes. We further show gonadotrope-specific upregulation of GnRHR protein (but not mRNA levels) following leptin stimulation. In order to try and understand this post-transcriptional regulation, we tested candidate miRNAs (identified with in silico analysis) that may be binding the Gnrhr mRNA. We show significant up-regulation of one of these miRNAs in our gonadotrope-Lepr-null females. The evidence provided here, combined with our previous work, lay the foundation for metabolically-regulated post-transcriptional control of the gonadotrope. We discuss possible mechanisms, including miRNA regulation and the involvement of the RNA binding protein, Musashi. We also demonstrate how this regulation may be vital for the dynamic remodeling of gonadotropes in the cycling female. Finally, we propose that the leptin receptivity of both the hypothalamus and the pituitary are vital for the body’s ability to delay or or slow reproduction during periods of low nutrition.